Impact of Cochlear Implant Array Placement on Speech Perception - Lo Russo, Francesco; Conte, Giorgio; Di Berardino, Federica; Cavicchiolo, Sara; Casale, Silvia; Caschera, Luca; Lombardi, Luciano; Triulzi, Fabio; Zanetti, Diego (Clinical neuroradiology (Munich), 2022)
Purpose To assess the role of flat panel computed tomography (FPCT) in the evaluation of cochlear implant (CI) electrode position and its relation to speech perception. Methods From March 2015 to March 2019, we retrospectively enrolled deaf subjects ≥ 18 years who underwent unilateral CI by one surgeon, imaged with FPCT and assessed with disyllabic words score before CI and at 6 months of follow-up. We calculated the disyllabic score difference before CI and after CI (ΔSDS) and divided the subjects in favorable and unfavorable outcome groups using the median ΔSDS as a cutoff. We compared the demographic, clinical, electrode characteristics, and the CI positioning variables scalar position, surgical insertion depth (SID), linear insertion depth (LID), angular insertion depth (AID) and wrapping factor (WF). Results We studied 50 subjects (F/M = 27/23; median age = 60.5 years, IQR: 50–70 years). The median ΔSDS was 80% (interquartile range [IQR]: 60–100%) in quiet and 80% (IQR: 47.5–100%) in noise. Of the subjects 23 demonstrated a favorable outcome and had earlier age at CI (median 52 years; IQR 45–67 years versus median 62 years; IQR: 56–71 years p = 0.032) and a significantly higher SID (median: 4.02 mm IQR: 3.00–5.35 mm versus median: 2.94 mm IQR: 2.06–3.90 mm; p = 0.029). No difference was found for LID ( p = 0.977), AID ( p = 0.302), and WF ( p = 0.224). A logistic regression model built with the age at CI, number of CI electrodes, and the SID was significant χ2 ((df = 3, N = 50) = 14.517, p = 0.002). The model explained 33.7% (Nagelkerke R2) of ΔSDS variance and correctly classified 76% of the cases. Conclusion The SID measured by FPCT predicts the ΔSDS at 6 months follow-up, alongside with age at implantation and number of CI electrodes.